Where you live shapes who you are: morphological changes in urban Triatoma infestans - Piccinali, Romina V.; Nattero, Julieta; Cano, Florencia; Sánchez-Casaccia, Paz; Carbajal-de-la-Fuente, Ana L. (Frontiers in Insect Science, 2025)
IntroductionUrbanization has transformed landscapes, driving ecological and morphological changes in insects. Chagas, traditionally a multidimensional rural problem, is increasingly reported in urban areas. Triatoma infestans, the primary vector of Chagas disease in the Southern Cone, has been reported in urban centers of San Juan, Argentina, for decades. Using morphometric and colorimetric analyses, we assess how urbanization influences the morphology and coloration of T. infestans.Materials and MethodsA total of 105 adults from five urban and one rural population of San Juan were analyzed.Wings, pronota, heads, and legs were measured and compared between populations and sexes. Principal Component and Canonical Variate Analyses were performed to assess shape variations. Kruskal-Wallis and Wilcoxon tests, and linear models examined size differences. Colorimetric analyses searched for wing and connexivum color differences between individuals.ResultsMultivariate analyses revealed significant morphological differentiation of wing, pronotum, and head shapes, primarily distinguishing the rural Valle Fértil from urban populations. Centroid size analyses indicated that rural individuals exhibited larger body structures, a pattern generally consistent across sexes. Furthermore, leg morphology also varied, with Valle Fértil insects possessing greater femur length and width compared to their urban counterparts. No significant color differences were found across populations or sexes.DiscussionUrban T. infestans exhibit size reductions, aligning with Schofield’s simplification hypothesis and possibly influenced by the Urban Heat Island effect. Shape changes, more pronounced in wings and pronota, suggest other influences beyond the rural-urban gradient, potentially including developmental plasticity, flight demands, and genetic drift. These findings underscore the need for urban-specific Chagas disease control strategies and further research on the evolutionary dynamics of T. infestans in urban environments.